The Councils of War in Fight for Leningrad - Valery Pavlovich Gridnev; Igor Vitalyevich Politov (Управленческое консультирование)
The article is devoted to organizing activity of military-political bodies - bodies of military management: The Council of War of troops of the Northwest direction, the Council of War of defense of Leningrad, the Council of War of the Leningrad front in fight for Leningrad. Relevance of a subject, structure of the Councils of War, plans of their activity, distribution of a predmetovedeniye and powers between members of the Councils of War, the translation of economy with peace on the martial law reveal. Results of reorganization of the national economy of the blockade city are presented. Courage and labor heroism of residents of the city front and staff of Field Army are shown in article.